The Relationship of Knowledge and Attitude with Community Anxiety Level in Facing Covid-19 Pandemic - Dwi Nur Aini; Arifianto Arifianto; Mohammad Arifin Noor (GLOBAL HEALTH SCIENCE GROUP, 2021)
Coronavirus disease 2019 (COVID-19) causes considerable morbidity and mortality since December 2019. This virus is spreading very rapidly on a global scale. The prevalence of COVID-19 continues to increase and global health emergency must be addressed immediately. Conditions pandemic will provide impact psychological one only anxiety. Anxiety is an emotional condition characterized by excessive anxiety overvarious events of daily life. The threat in the midst of the Covid-19 pandemic has the potential to continue to increase and become a threat to the mental health condition of people. Anxiety could lower their body immune and in the long term, it could lead to hopelessness. One of the factors that influence public anxiety in dealing with the COVID-19 pandemic is the level of knowledge and attitude. The purpose of this study was to determine the relationship between knowledge and attitudes with the level community anxiety in facing Covid 19 pandemic. This type of research was a quantitative research using a pre-experimental type with a one-group pretest-posttest design without a control group design. Sampling technique used purposive sampling of 30 respondents with Spearman Rank statistical test obtained P Value 0.001 (P value < (0.05)) for the knowledge variable and P Value 0.009 (P value < (0.05) for the attitude variable. There is a relationship between knowledge and attitudes with the level of community anxiety in facing Covid-19 pandemic.